On the key revocation schemes in wireless sensor networks - Mall, Dieynaba; Konaté, Karim; Pathan, Al-Sakib Khan (2013)
Among all security issues, key management is the most attractive mechanism to ensure security of applications and network services in wireless sensor networks. Key management includes two important aspects namely: Key distribution, which constitutes the task of distributing secret keys to nodes in the network and Key revocation, which refers to the task of securely withdrawing the key information relating to any compromised network node. While in the literature, key distribution has been extensively studied; key revocation has received relatively little attention. In this paper, we present a survey on the state-of-the-art key revocation techniques and also present the security and performance analysis that highlights the advantages and disadvantages of each scheme.